Evaluation of noise transfer path contributions using virtual springs with infinite stiffness. (July 2021) - Kim, Jun Gu; Nam, Kyoung-Uk; Kang, Yeon June
Highlights: A new method for evaluating the transfer path is proposed. This method is based on an FRF-based substructuring technique. The proposed method uses the concept of a virtual spring with infinite stiffness. This technique is valid for vehicle components that have difficult-to-remove parts. This method is easier to implement and is more applicable than the other methods. Abstract: Transfer path analysis (TPA) is a process that can identify the priorities for a variety of possible paths from a noise and vibration source to an output. To reduce noise response, efficient transfer paths for the transmission and isolation of noise need to be identified. This study proposes a novel TPA method that is based on a dynamic substructuring model, which uses the frequency response function (FRF) information of a base system to evaluate the effect of increasing stiffness at the measurement points, without actually modifying the stiffness. In the proposed method, a spring with infinite stiffness is added to a specific transfer path among a variety of possible paths; this addition is tantamount to eliminating the specific path. Thus, the virtual spring helps to reduce the contribution of the specific path significantly. This method is easier to implement and is more applicable than existing TPA methods (i.e., classical TPA and operational TPA). This is because it does not require part removal or the correlation information among signals. To verify the feasibility of the FRF-based contribution analysis method, it was applied to a road noise phenomenon. The test results show that the proposed method can be applied to the TPA of suspension linkages and vehicle body.